2006
DOI: 10.1177/0964663906063579
|View full text |Cite
|
Sign up to set email alerts
|

The Insanities of Reproduction: Medico-legal Knowledge and the Development of Infanticide Law

Abstract: Drawing on autopoiesis theory, Ward (1999) challenges the established view that the adoption of the English infanticide law in 1922 (amended 1938) is an example of the medicalization of law, insisting that the 1922 Act embodied a lay biological theory and that contemporary psychiatric theories of the ‘insanities of reproduction’ focused on socio-economic, rather than biological, stressors. Both the medicalization and autopoiesis interpretations of infanticide law are misplaced. A broader review of the medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Infanticide law is based in highly problematic notions of an unstable and 'hysterised' feminine body and mind: ideas active since Hippocrates mooted that postnatal 'madness' might be 'lactational insanity', milk going to the brain. Although there is scant evidence for insanity due to lactation, and the concept relates more to issues of exhaustion and malnutrition in poor working mothers which were urgent at the time of the original enactment of the Infanticide Act in 1922 (Ward 1999;Kramar and Watson 2006), the Law Commission recently refused to alter the Act to remove references to lactation (2006, p. 159). The law still provides for a charge of manslaughter rather than murder if ''at the time of the act or omission the balance of [the mother's] mind was disturbed by reason of her not having fully recovered from the effect of giving birth to the child or by reason of the effect of lactation consequent upon the birth of the child''.…”
Section: Legal Caricature/legal Concessionmentioning
confidence: 97%
“…Infanticide law is based in highly problematic notions of an unstable and 'hysterised' feminine body and mind: ideas active since Hippocrates mooted that postnatal 'madness' might be 'lactational insanity', milk going to the brain. Although there is scant evidence for insanity due to lactation, and the concept relates more to issues of exhaustion and malnutrition in poor working mothers which were urgent at the time of the original enactment of the Infanticide Act in 1922 (Ward 1999;Kramar and Watson 2006), the Law Commission recently refused to alter the Act to remove references to lactation (2006, p. 159). The law still provides for a charge of manslaughter rather than murder if ''at the time of the act or omission the balance of [the mother's] mind was disturbed by reason of her not having fully recovered from the effect of giving birth to the child or by reason of the effect of lactation consequent upon the birth of the child''.…”
Section: Legal Caricature/legal Concessionmentioning
confidence: 97%
“…and expertise, it was only a correction of the lay theory embodied in the original legislation, reflective of a primarily socioeconomic, as opposed to biomedical, psychiatric orthodoxy. Thus, despite the reservations we have expressed elsewhere regarding Ward's characterization of the contemporary psychiatric thinking as lacking reductively biomedical and otherwise biological strands (Kramar and Watson 2006), his argument that no such theory was the basis of the biologism of either piece of English legislation seems sound.…”
Section: Ward's Account Of the Passage Of The English Actsmentioning
confidence: 80%
“…We have argued elsewhere (Kramar and Watson 2006) that, while Ward successfully demonstrates that the 1922 Act did not reflect contemporary psychiatric orthodoxy and, indeed, that the legislators were not concerned with psychiatric theory, there was a clear strand of distinctly biological theorizing that ran alongside, and was entangled with, the dominant socioeconomic theories. We also argued that infanticide law may have facilitated the medicalization of infanticide in the decades between its passage and the present day, whatever the intentions and knowledge-base of legislators.…”
Section: Reads As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although infanticide allows for a more lenient approach, feminists have criticised this law on the ground that it medicalises the offender, explaining her crime as the product of a biologically produced mental disturbance and failing to acknowledge any social, economic, and political causes (Morris and Wilczynski, 1993). However, research into the history of this law shows that the mental disturbance rationale was based on a lay understanding of infanticide which could take account of the social and other causes of infanticide (Ward, 1999;Kramar, 2005;Kramar and Watson, 2006;Brennan, 2013b). In terms of how the law has been applied in practice, research has shown that it allows for 'covert recognition' of social causes (Morris and Wilczynski, 1993), and that it operates as a 'legal device' to facilitate lenient treatment of at least some girls and women who kill their babies at birth (Mackay, 1993, p. 29).…”
Section: Impact Of Mental State On Mental Fault Requirementsmentioning
confidence: 99%